Al-Balāghah in the Thought of Al-Zamakhsharī: A Stage in the Maturation of Research on Qur’anic Inimitability (Iʿjāz al-Qurʾān) - Khaled Yahya Abdurrahman; Noza Aflisia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Zamakhshari's effort is limited to the practical aspect, and highlights the role of the science of eloquence in preparing the interpreter of the Book of God, and whether Zamakhshari added new to the rhetorical standards, and models of his interpretation showing his use of rhetorical rules in understanding the Book of God. This research is a desk research. The data obtained is processed by content analysis techniques. As for the results of the research, Zamakhshari is the pillar sought by the science of interpretation; Because it is his goal and purpose, just as the science of rhetoric that Zamakhshari employed in revealing the miracle of the Qur’an is closely related to the science of semantics. Zamakhshari tries to interpret the Qur’an by organizing the vocabulary of the material into a meaning that brings it together in a single structure within a single context. He draws attention to the effect of speech systems on the meaning, so he looks at the Qur’an with the look of the verified examiner, and accordingly, the meaning is interpreted and interpreted. It provokes a dialogue in one aspect, paving the way for another dialogue to move to another verse, and he thus follows the approach of Al-Jurjani in using dialogue to reach the desired goal. He cites poetry in his explanations, and poetry was an important aspect for him to infer the validity of his interpretations.